Enhanced bioavailability through quality by design optimization of ceritinib nanostructured lipid carriers: Formulation, characterization, and stability evaluation - Kunchithapatham Janakiraman, Katla Venu Madhav, Sunil Kumar Chaitanya Padavala, Naga Haritha Pamujula (Journal of Applied Pharmaceutical Science, 2024)
Ceritinib is a lung cancer treatment that inhibits the Anaplastic Lymphoma Kinase (ALK). ALK is a protein involved in cell signaling and growth regulation. Initially discovered in anaplastic large cell lymphoma, ALK has since been found to play critical roles in various cancers and neurodevelopmental processes. Targeted therapies that inhibit ALK have revolutionized treatment for ALK-positive cancers, improving outcomes significantly. Research continues to explore ALK’s intricate mechanisms and its potential as a therapeutic target beyond oncology, highlighting its broad biological importance. In this study, Ceritinib-drug loaded nanostructured lipid carriers were produced using a modified homogenization process by increasing number of homogenisation cycles followed by probe sonication. A central composite design was utilised to investigate the effect of liquid lipid (A), emulsifier (B), and co-surfactant (C) concentrations on particle size (Response 1) and entrapment efficiency (Response 2). The specific impacts of these parameters on particle size and entrapment efficiency were shown in response surfaces, using Derringer’s desirability technique. Formulation 8 with 0.1% Capmul, 0.15% egg lecithin, and 0.37% poloxamer 188 was subjected to further evaluation as it had minimal particle size and maximum entrapment efficiency. The SEM analysis was performed to confirm the size of the particle which was within the nano range. The in vitro studies indicated the maximum drug release (84.6%±2.3% in 12 hours) from that of the marketed formulation (54.2%±2.5% in 12 hours). After 90 days of stability testing, there was no significant variation (p < 0.05) in parameters like particle size and entrapment efficiency.
Keywords: Ceritinib, nanostructured lipid carriers, bioavailability enhancement, BCS class IV, anti-cancer, probe sonication, statistically significant